Dimensions of Love and Human Wisdom: Jalaluddin Rumi's View in Etnosufistic Perspective - Pangulu Abdul Karim; Miswar Miswar; Muqarramah Sulaiman Kurdi (IAIN Ponorogo, 2022)
This study aims to describe the dimensions of love and human wisdom according to Jalaluddin Rumi. This research is qualitative research with a library research model studied with an ethnosufistic approach. The primary data of the research is the book of Fīhī mā fīh by Jalaluddin Rumi. The data collection technique is done by documentation. The researcher systematically documents the data of the trilogy of love and human wisdom in the book according to the specified theme/fasl. Meanwhile, data analysis was carried out descriptively-interpretatively. The research results mention; human love and wisdom, according to Rumi, is divided into three dimensions; man to Allah SWT; human to human; and humans to nature. This is stated in the book of Fīhī mā fīh Article 1